2020
DOI: 10.1371/journal.pone.0226544
|View full text |Cite
|
Sign up to set email alerts
|

Potential socioeconomic impacts from ocean acidification and climate change effects on Atlantic Canadian fisheries

Abstract: Ocean acidification is an emerging consequence of anthropogenic carbon dioxide emissions. The full extent of the biological impacts are currently not entirely defined. However, it is expected that invertebrate species that rely on the mineral calcium carbonate will be directly affected. Despite the limited understanding of the full extent of potential impacts and responses there is a need to identify potential pathways for human societies to be affected by ocean acidification. Research on these social implicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…All these studies make clear that our capacity to replicate environmental and biological complexity in experimental studies is limited, yet more sophisticated and longer term studies are critical to enable further understanding of physiological mechanisms, energetic balances in organisms, and population dynamic consequences of OA in marine species. A handful of other studies, including responses through trophic webs (e.g., Jin et al, 2015) and other ecological interactions (e.g., Fay et al, 2017;Schulz et al, 2017;Gilbert, 2020;Raven et al, 2020;Tester et al, 2020;Wilson et al, 2020), have suggested potentially larger but varied ecological and ecosystem consequences of OA in the GOM. Thus, a better integration of our current knowledge, predictive capability, and collaboration will be key to addressing management and societal changes that ameliorate OA consequences in the region and preserve the sustainability of marine resources and the services they provide to the GOM.…”
Section: Sensitivity Of Gom Fauna To Oamentioning
confidence: 99%
“…All these studies make clear that our capacity to replicate environmental and biological complexity in experimental studies is limited, yet more sophisticated and longer term studies are critical to enable further understanding of physiological mechanisms, energetic balances in organisms, and population dynamic consequences of OA in marine species. A handful of other studies, including responses through trophic webs (e.g., Jin et al, 2015) and other ecological interactions (e.g., Fay et al, 2017;Schulz et al, 2017;Gilbert, 2020;Raven et al, 2020;Tester et al, 2020;Wilson et al, 2020), have suggested potentially larger but varied ecological and ecosystem consequences of OA in the GOM. Thus, a better integration of our current knowledge, predictive capability, and collaboration will be key to addressing management and societal changes that ameliorate OA consequences in the region and preserve the sustainability of marine resources and the services they provide to the GOM.…”
Section: Sensitivity Of Gom Fauna To Oamentioning
confidence: 99%
“…Adaptation strategies to combat ocean acidification are challenging, particularly when they are combined with other stressors like eutrophication (Wilson et al 2020). Recent reviews of climate effects on coral reefs indicate a rapid reduction in greenhouse gas emissions that stabilize global temperatures and CO 2 is the only viable long‐term solution for ensuring survival of coral reefs (Munday et al 2008; Hoegh‐Guldberg et al 2017).…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Maintaining seagrass can also help protect coral reef habitats from ocean acidification (Table 4; Liu et al 2020). For shellfish, aquaculture has been considered a possible adaptation strategy because in facilities pH can controlled (Wilson et al 2020). Similar to strategies for sea level rise, managers can cultivate a diversity of habitats that may establish unique populations and broaden the gene pool which may help the systems adapt to ocean acidification.…”
Section: Ocean Acidificationmentioning
confidence: 99%
“…Adaptation strategies to combat ocean acidifi cation are challenging, particularly when they are combined with other stressors like eutrophication (Wilson et al 2020 ). Recent reviews of climate effects on coral reefs indicate a rapid reduction in greenhouse gas emissions that stabilize global temperatures and CO 2 is the only viable long-term solution for ensuring survival of coral reefs (Munday et al 2008 ;Hoegh-Guldberg et al 2017 ).…”
Section: Adaptation Strategiesmentioning
confidence: 99%
“…Maintaining seagrass can also help protect coral reef habitats from ocean acidification (Table 4 ; Liu et al 2020 ). For shellfi sh, aquaculture has been considered a possible adaptation strategy because in facilities pH can controlled (Wilson et al 2020 ). Similar to strategies for sea level rise, managers can cultivate a diversity of habitats that may establish unique populations and broaden the gene pool which may help the systems adapt to ocean acidifi cation.…”
Section: Adaptation Strategiesmentioning
confidence: 99%